The STYLISTIC USAGE IN PRELIMINARY INVESTIGATION REPORT IN MURDER CASE - Alfiah Pratiwi,; Waode Surya Darmadali, (Elite : English and Literature Journal, 2022)
This research aims to find out what stylistic devices that are occurred in Preliminary Investigation Report of murder cases, and describe the use of the stylistic devices in the analysis of confession and truth of a suspect that has been confirmed as cases committed in a criminal conspiracy. This research is a descriptive qualitative assisted with quantitative data. This research took place in the Makassar State Prosecutor’s Office and was held during April until July 2014. The data sources of this research are the Preliminary Investigation Report of three murder cases. The findings show that (1) the types of schemes that are most frequently used are parenthesis and periphrasis. The tropes which are most frequently used are euphemism and hyperbole. (2) The stylistic devices can be used to indicate and analyze confession and the truth. The suspect in the murder case mostly used hyperbole when they confessed the crime and showed their true remorse. They used euphemisms to mention the condition of their victims’ families. The truth can be revealed by seeing the consistency of their words and their arrangement of words.